CROCUFID: A Cross-Cultural Food Image Database for Research on Food Elicited Affective Responses - Toet, Alexander; Kaneko, Daisuke; de Kruijf, Inge; Ushiama, Shota; van Schaik, Martin G.; Brouwer, Anne-Marie; Kallen, Victor; van Erp, Jan B. F. (Frontiers in Psychology, 2019)
We present CROCUFID: a CROss-CUltural Food Image Database that currently contains 840 images, including 479 food images with detailed metadata and 165 images of non-food items. The database includes images of sweet, savory, natural, and processed food from Western and Asian cuisines. To create sufficient variability in valence and arousal we included images of food with different degrees of appetitiveness (fresh, unfamiliar, molded or rotten, spoiled, partly consumed). We used a standardized photographing protocol, resulting in high resolution images depicting all food items on a standard background (a white plate), seen from a fixed viewing (45 deg) angle. CROCUFID is freely available under the CC-By Attribution 4.0 International license and hosted on the OSF repository. The advantages of the CROCUFID database over other databases are its (1) free availability, (2) full coverage of the valence - arousal space, (3) use of standardized recording methods, (4) inclusion of multiple cuisines and unfamiliar foods, (5) availability of normative and demographic data, (6) high image quality and (7) capability to support future (e.g. virtual and augmented reality) applications. Individuals from the UK (N=266), North-America (N=275) and Japan (N=264) provided normative ratings of valence, arousal, perceived healthiness, and desire-to-eat using visual analogue scales (VAS). In addition, for each image we computed 17 characteristics that are known to influence affective observer responses (e.g., texture, regularity, complexity, colorfulness). Significant differences between groups and significant correlations between image characteristics and normative ratings were in accordance with previous research, indicating the validity of CROCUFID. We expect that CROCUFID will facilitate comparability across studies and advance experimental research on the determinants of food-elicited emotions. We plan to extend CROCUFID in the future with images of food from a wide range of different cuisines and with non-food images (for applications in for instance neuro-physiological studies). We invite researchers from all parts of the world to contribute to this effort by creating similar image sets that can be linked to this collection, so that CROCUFID will grow into a truly multicultural food database.